The pursuit of financial stability post Global Financial Crisis : is Twin Peaks the cure for South Africa? - Van Heerden, C.M. (Corlia) (University of Pretoria, 2019)
Mini Dissertation (LLM)--Universiity of Pretoria, 2019.